Can Incarcerated Felons Be (Re)integrated into the Political System? Results from a Field Experiment. Issue 4 (18th December 2014) - Gerber, Alan S.; Huber, Gregory A.; Meredith, Marc; Biggers, Daniel R.; Hendry, David J.
<x xml:space="preserve">Abstract</x> How does America's high rate of incarceration shape political participation? Few studies have examined the direct effects of incarceration on patterns of political engagement. Answering this question is particularly relevant for the 93% of formerly incarcerated individuals who are eligible to vote. Drawing on new administrative data from Connecticut, we present evidence from a field experiment showing that a simple informational outreach campaign to released felons can recover a large proportion of the reduction in participation observed following incarceration. The treatment effect estimates imply that efforts to reintegrate released felons into the political process can substantially reduce the participatory consequences of incarceration.